How Can We Redesign Dissection Lessons in the High School Life Science Classroom? Considerations for a Meaningful 21st Century Learning Experience - Mager, Amanda Marie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Dissections in the life science classroom have become less prevalent as science educators have questioned what these experiences teach. Constructivist theorists of education have long suggested redefining the purpose of dissections to better fit the needs of student learning in the 21st century. Using the Next-Generation Science Standards framework, educators can create more meaningful dissections by incorporating opportunities for students to engage in true scientific inquiry. For dissection experiences to be worthwhile and meaningful for students, the activity must be carefully planned and worked into a unit where students can use such an experience to help answer a central unit question. Innovative 21st century dissection activities that allow students to engage in true scientific inquiry are addressed.